LIMITED JOINT MOBILITY IN A CHILD WITH TYPE 1 DIABETES MELLITUS. - Mohammad H. Al-Qahtani; Fai A. AlQahtani (Case Reports in Medicine)
Chronic uncontrolled type 1 diabetes mellitus (type 1DM) is a very major risk for chronic systemic complications; specifically, the microvascular and macrovascular ones. Limited joint mobility (LJM) is a rare disease that complicates all types of diabetes and might indicate the high-risk odd for the diabetic patients to develop microvascular complications. We are reporting a 13-year-old female child with chronic uncontrolled type 1DM presenting with full blown clinical picture of bilateral hand LJM associated with significant growth failure yet has no clinical or biochemical evidence of microvascular complications. Literature research studies have emphasized the rarity of this manifestation in pediatric type 1 diabetic patients; however, it is an important clue and warning sign for microvascular complication occurrence in these patients.